Молодежь и свободное время - Бубнова Н. И. (Методическое пособие в помощь лектору, 1970)
Экземпляры: КХ (20130124) / Инвентарный номер: 0199387 / Цена: 0.03 / Сис.шифр: 3КСМ / Авт.знак: Б 90 / ГРНТИ: 11 / ББК: 66